Trace determination of safranin O dye using ultrasound assisted dispersive solid-phase micro extraction: Artificial neural network-genetic algorithm and response surface methodology - Dil, Ebrahim Alipanahpour; Ghaedi, Mehrorang; Asfaram, Arash; Mehrabi, Fatemeh; Bazrafshan, Ali Akbar; Ghaedi, Abdol Mohammad (Ultrasonics sonochemistry, 2016)
[Display omitted] •The Fe2O3-NPs-AC were used as adsorbent for extraction of SO from water samples.•Ultrasound-assisted extraction was used for SO extraction.•Optimization of ultrasound-assisted extraction process using response surface methodology (RSM).•Fe2O3-NPs-AC demonstrated high recovery (93.27–99.41%) and low LOD (6.3ngmL−1).•Under the optimal conditions, a linear range from 25 to 3500ngmL−1 was obtained. In this study, ultrasound assisted dispersive solid-phase micro extraction combined with spectrophotometry (USA-DSPME-UV) method based on activated carbon modified with Fe2O3 nanoparticles (Fe2O3-NPs-AC) was developed for pre-concentration and determination of safranin O (SO). It is known that the efficiency of USA-DSPME-UV method may be affected by pH, amount of adsorbent, ultrasound time and eluent volume and the extent and magnitude of their contribution on response (in term of main and interaction part) was studied by using central composite design (CCD) and artificial neural network-genetic algorithms (ANN-GA). Accordingly by adjustment of experimental conditions suggested by ANN-GA at pH 6.5, 1.1mg of adsorbent, 10min ultrasound and 150μL of eluent volume led to achievement of best operation performance like low LOD (6.3ngmL−1) and LOQ (17.5ngmL−1) in the range of 25–3500ngmL−1. In following stage, the SO content in real water and wastewater samples with recoveries between 93.27–99.41% with RSD lower than 3% was successfully determined.